Diastolic dysfunction grade in acute coronary syndromes: Application of 2016 American Society of Echocardiography/European Association of Cardiovascular Imaging recommendations. (15th April 2020) - Bursi, Francesca; Persampieri, Simone; Sabatelli, Ludovico; Bencini, Chiara; Santangelo, Gloria; Bosotti, Laura; Tayar, Alessandro; Valli, Federica; Ferrante, Giulia; Caretta, Alessandro; Torta, Daniela; Massironi, Laura; et al.
Abstract: Background: Diagnosis and grading of diastolic dysfunction (DD) is challenging, with different studies using heterogeneous criteria and guidelines not routinely applied in clinical practice. Our aim was to apply the 2016 American Society of Echocardiography/European Association of Cardiovascular Imaging classification of DD among a contemporary population of patients with acute coronary syndromes (ACS) by analyzing its correlation with N-terminal pro b-type natriuretic peptide (NT-proBNP) and impact on clinical outcomes. Methods: Independent investigators blinded to each other and to the clinical history reviewed digitally stored images to apply 2016 and 2009 DD definitions to 380 patients (mean age 66 ± 13 years, 75% men) with ACS admitted to the coronary care unit between January 2016 and March 2018. Results: DD was frequent with both definitions, yet the concordance was weak (kappa =0.21, p < 0.01). Inter-observer reliability was greater by applying the 2016 algorithm (kappa = 0.89, p < 0.001). There was a significant correlation between NT-proBNP and worsening DD (Spearman's rho r = 0.54 for 2016 and r = 0.24 for 2009 algorithms, both p < 0.001). Worse DD was associated with worse clinical presentation and increased risk of events (HR for the cumulative incidence of heart failure and death during follow-up 2.15 [95% CI 1.66–2.78, p < 0.001] and 1.82 [95% CI 1.39–2.40, p < 0.001] for 2016 and 2009 classifications, respectively, all p < 0.001). Conclusions: The agreement between 2016 and 2009 DD definitions was poor, with newer guidelines having grater interobserver reliability. The positive graded association between 2016 DD classification and NT-proBNP and its association with clinical outcomes provide a validation of the latest guideline algorithm in ACS patients. Highlights: DD is frequent with both 2009 and 2016 definitions among ACS patients. The agreement between 2016 and 2009 DD definitions is poor. A significant correlation between NT-proBNP and worsening 2016 DD is evident. Worse 2016 DD is associated with worse clinical presentation and increased risk of events.